2022
DOI: 10.3390/ijms232416104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Xyloglucan Endotransglycosylase/Hydrolase (XTH) Gene Family Members Expressed in Boehmeria nivea in Response to Cadmium Stress

Abstract: Xyloglucan endotransglycosylase/hydrolase (XTH) genes play an important role in plant resistance to abiotic stress. However, systematic studies of the response of Boehmeria nivea (ramie) XTH genes (BnXTHs) to cadmium (Cd) stress are lacking. We sought to identify the BnXTH-family genes in ramie through bioinformatics analyses and to investigate their responses to Cd stress. We identified 19 members of the BnXTH gene family from the ramie genome, referred to as BnXTH1-19, among which BnXTH18 and BnXTH19 were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Xyloglucan endotransglucosylase/hydrolase (XTH) is a key xyloglucan modifying enzyme belonging to the glycoside hydrolase 16 (GH16) family, which catalyzes the cleavage and polymerization of xyloglucan molecules to modify the celluline–xyloglucan complex structure of seed germination [ 17 , 18 ], and cell walls [ 19 ] and elongation [ 20 , 21 ]. XTHs, which are directly involved in the initial assembly and subsequent restructuring of primary cell walls [ 22 , 23 ], exhibit two diverse catalytic activities: xyloglucan endohydrolase (XEH) and xyloglucan endotransglycosylase (XET) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xyloglucan endotransglucosylase/hydrolase (XTH) is a key xyloglucan modifying enzyme belonging to the glycoside hydrolase 16 (GH16) family, which catalyzes the cleavage and polymerization of xyloglucan molecules to modify the celluline–xyloglucan complex structure of seed germination [ 17 , 18 ], and cell walls [ 19 ] and elongation [ 20 , 21 ]. XTHs, which are directly involved in the initial assembly and subsequent restructuring of primary cell walls [ 22 , 23 ], exhibit two diverse catalytic activities: xyloglucan endohydrolase (XEH) and xyloglucan endotransglycosylase (XET) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…XET is one of the most important parts of ancient machinery regulating cell wall modifications [ 32 ]. In different species, the XET gene is involved in seed germination [ 18 ], cell wall construction [ 33 ], and abiotic stress response [ 21 , 26 ], indicating that the function of the XET gene is significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in response to cadmium (Cd) stress, the expression of BnXTH1 , BnXTH3 , BnXTH6 , and BnXTH15 was observed to be upregulated in Boehmeria nivea . Conversely, BnXTH18 , BnXTH16 , BnXTH17 , and BnXTH5 exhibited notable downregulation under the same Cd stress conditions [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 53 MaXTHs have been identified in Genome A of banana, which were divided into 3 subclasses: Group I/II, Group IIIA and Group IIIB as other plants. Plant XTHs have been identified in many plants and the family member varies from 19 (Ma et al, 2022) to 61 (Song et al, 2018).…”
Section: Fucosylated Xygmentioning
confidence: 99%
“…To date, the XTH family has been identified in many plants. For example, there are 33 XTHs in Arabidopsis (Yokoyama and Nishitani, 2001), 56 in Nicotiana tabacum (Wang et al, 2018), 61 in Glycine max (Song et al, 2018), 34 in Citrus sinensis (Li et al, 2019a), 48 in Ananas comosus (Li et al, 2019b), 36 in Ipomoea batatas (Zhang et al, 2023), 19 in Boehmeria nivea (Ma et al, 2022), 14 in Camellia sinensis (Wu et al, 2021), respectively.…”
Section: Introductionmentioning
confidence: 99%